Impact of Chitosan Nanoparticles Loaded Oxytetracycline Hydrochloride for Drug Delivery Against Flavobacterium Columnare Isolated From Common Carp (Cyprinus CarpioL.) - Ali, Medyan N; AL-Faragi, Jamal K. A; Al-Saadi , Tagreed M (International Journal of Psychosocial Rehabilitation, 2020)
This present study investigates a new method for oxytetracycline (OTC) application through the use of Chitosan nanoparticles (ChNPs) as drug delivery, used the ionic gelation method for preparation of chitosan nanoparticles and it's loaded. Also characterized the properties particle size, shape, encapsulation efficiency, and antibacterial activity against F.columnare isolated from common carp. The formulations are spherical.The diameter of chitosan nanoparticles size varying from 10-15 nm and chitosan nanoparticles loaded oxytetracycline(ChNPs-OTC) in size about 20 nm. With high encapsulation efficiency ranging from 99.4% to 99.8%. Antibacte¬rial activity was in vitro against Flavobacterium columnare using a good diffusion method, 5 concentrations of ChNPs-OTC (20,15,10,5, and 2.5 µg/ml) with 20ug/ml of blank oxytetracycline as control positive. The higher inhibition zone was recorded in ChNPs-OTC with higher concentration. These results suggest that ChNPs-OTC show possible using the delivery of drugs and improved treatment effectiveness for bacterial fish diseases.